Ventral tegmental area glutamate neurons co-release GABA and promote positive reinforcement - Ji Hoon Yoo (Nature Portfolio, 2016)
Ventral tegmental area (VTA) is involved in reward behaviours, but the precise contribution of VTA glutamatergic neurons to this process is not known. Here the authors show that phasic but not sustained optogenetic stimulation of VTA glutamatergic neurons is rewarding and involves co-release of GABA.